Traffic Performance Analysis on Road Sections Affected by the Construction of the Underpass Leading to the Indonesian National Armed Forces (TNI) Headquarters - Arul Sugi Jauharul; Alfandias Seysna Putra; Ardi Pratama (International Journal Labs, 2026)
The Mabes Hankam intersection is one of the main intersections that frequently experiences traffic congestion, particularly during peak hours in the morning and evening. This problem leads to delays, long queues, and a decrease in the quality of road service. This research aims to evaluate the traffic performance at the intersection and provide an overview of possible solutions to reduce congestion levels while ensuring that access for vehicles heading to the TNI Headquarters is not disrupted. The data used in this study include traffic volume and road capacity, obtained from PT. Armada and the Ministry of Public Works. The analysis was carried out using the Indonesian Highway Capacity Guidelines (PKJI 2023) with performance indicators such as degree of saturation (DS), average delay, queue length, and Level of Service (LOS). The results indicate that during peak hours, the degree of saturation approaches or exceeds 1.0, with the level of service ranging from LOS E to F, indicating saturated traffic conditions and frequent congestion. This condition highlights the need for appropriate traffic management efforts, such as the construction of an underpass, signal timing adjustments, or other traffic management strategies to mitigate congestion impacts. This research is expected to provide practical benefits as input for relevant institutions in formulating traffic control strategies in high-volume areas. In addition, it also contributes academically as a reference for the development of transportation studies, particularly in evaluating the performance of urban intersections with high traffic density.